2019
DOI: 10.3390/agronomy9070374
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergy from Periodically Waterlogged Cropland in Europe: A First Assessment of the Potential of Five Perennial Energy Crops to Provide Biomass and Their Interactions with Soil

Abstract: Harvesting of silage maize in late autumn on waterlogged soils may result in several ecological problems such as soil compaction and may subsequently be a major threat to soil fertility in Europe. It was hypothesized that perennial energy crops might reduce the vulnerability for soil compaction through earlier harvest dates and improved soil stability. However, the performance of such crops to be grown on soil that are periodically waterlogged and implications for soil chemical and microbial properties are cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 50 publications
3
14
0
1
Order By: Relevance
“…Under such conditions, perennial BCS, such as willow short rotation coppice, are suitable options [198]. Recently, several perennial crops were also found to be promising for waterlogged sites [214]. Whereas, these results draw on pot trials and need further evaluation under field conditions.…”
Section: The Potential Growth Suitability Of Bioenergy Crops On Margimentioning
confidence: 99%
“…Under such conditions, perennial BCS, such as willow short rotation coppice, are suitable options [198]. Recently, several perennial crops were also found to be promising for waterlogged sites [214]. Whereas, these results draw on pot trials and need further evaluation under field conditions.…”
Section: The Potential Growth Suitability Of Bioenergy Crops On Margimentioning
confidence: 99%
“…Other authors are more cautious with their statements. Zilverberg et al [86] mentioned that it tolerates moderate flooding while Bauböck et al [87] acknowledged the resistance of S. perfoliatum to water. This observation is supported by Ruf et al [88], who demonstrated that S. perfoliatum not only can withstand waterlogging but benefits from it, doubling the amount of biomass production after waterlogging during the winter period.…”
Section: Agroclimatic Requirementsmentioning
confidence: 99%
“…Despite JA can well adapt to dry conditions, the plant has low water use efficiency (WUE) due to its poor stomatal regulation. In a recent study, Ruf et al [33] showed significantly better WUEs in excess soil moisture conditions than in non-excess treatment, for JA plants grown in pots. However, studies conducted in Italy have demonstrated the higher adaptability of this crop to arid environments as compared to other crops such as chicory, kenaf and sweet sorghum [19,21].…”
Section: Droughtmentioning
confidence: 92%
“…However, in these conditions JA could be cultivated as a perennial crop, targeting to the high stem storage and early tuberization. Even though JA has shown to be tolerant to waterlogging condition [33], excessive soil moisture content has a different negative effect: it reduces plant emergence, increases stalk development, decreases tuber growth and enhances plant vulnerability to pathogens. Overall, fructan yield, tuber size and shape are affected by soil type.…”
Section: Soil Typementioning
confidence: 99%